2006
DOI: 10.1002/cne.21155
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde analyses of spinothalamic projections in the macaque monkey: Input to posterolateral thalamus

Abstract: The distribution of retrogradely labeled spinothalamic tract (STT) neurons was analyzed in macaque monkeys following variously sized, physiologically guided pressure or iontophoretic injections of cholera toxin subunit B (CTb) in order to determine whether different STT termination sites receive input selectively from different sets of STT cells. This report focuses on posterolateral thalamus, where prior anterograde tracing observations identified the posterior part of the ventromedial nucleus (VMpo) as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 45 publications
(73 reference statements)
9
51
0
2
Order By: Relevance
“…Each method has confirmed that neurons of the dorsal horn send projections to the posterior thalamus. Craig and colleagues have recently advanced a hypothesis that marginal zone neurons preferentially target VMpo and that VPL receives input from neurons located within the deeper laminae (Craig 2006;Craig and Zhang 2006). The present study confirms that the posterior thalamus receives a relatively high proportion of marginal zone projections.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Each method has confirmed that neurons of the dorsal horn send projections to the posterior thalamus. Craig and colleagues have recently advanced a hypothesis that marginal zone neurons preferentially target VMpo and that VPL receives input from neurons located within the deeper laminae (Craig 2006;Craig and Zhang 2006). The present study confirms that the posterior thalamus receives a relatively high proportion of marginal zone projections.…”
Section: Discussionsupporting
confidence: 86%
“…The input to the posterior thalamus from the STT has been studied using degeneration (Boivie 1979;Mehler 1969;Mehler et al 1960), retrograde (Craig 2006;Craig and Zhang 2006;Willis et al 2001), and anterograde tracing methods (Apkarian and Hodge 1989;Beggs et al 2003;Craig 2004;Gauriau and Bernard 2004a;Ralston and Ralston 1992;Stepneiwska et al 2003). Each method has confirmed that neurons of the dorsal horn send projections to the posterior thalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies suggest that thinfiber networks mediating pain and temperature connect from the superficial laminae of the dorsal horn via somatotopically arranged projections through the spinothalamic tract (STT) to a specific ventromedial posterior thalamic nuclei (VMPo), terminating in the contra-lateral posterior insular cortex (Craig et al, 1994(Craig et al, , 1999Blomqvist and Craig, 2000;Craig, 2003;Craig and Zhang, 2006) (but see Willis et al, 2002). Consistent with these projections, functional imaging of innocuous cooling as well as painful stimuli have revealed a cortically maintained somatotopic organization of the posterior insula with upper body afferents activating regions anterior to those of the lower body (Brooks et al, 2005;Hua le et al, 2005;Henderson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological evidence suggests that C‐fibre stimulation activates the mossy fibre input from the pontine nuclei 33, and that both A‐fibre and C‐fibre stimulation activates the climbing fibres 34, which transmit information from the inferior olive to the cerebellum. In addition, the zona incerta and the periaqueductal grey, two brain regions that deliver major inputs to the inferior olives, are known to relay both ascending nociceptive information 35, 36, 37, as well as descending cortical signals.…”
Section: Introductionmentioning
confidence: 99%